Redistribution and tax expenditures : the earned income tax credit - Eissa, Nada.; Hoynes, Hilary Williamson; National Bureau of Economic Research (Cambridge, MA : National Bureau of Economic Research, 2008)
This paper examines the distributional and behavioral effects of the Earned Income Tax Credit (EITC). We chart the growth of the program over time, and argue several expansions show that real responses to taxes are important. We use tax data to show the distribution of benefits by income and family size, and examine the impacts of hypothetical reforms (expansions and contractions) to the credit. Finally, we calculate the efficiency effects of marginal changes to EITC parameters. Targeting the EITC to lower-income families by raising the phase-out rate generates a welfare loss for single mothers, primarily because of the disincentive to enter the labor market and not the traditional hours-of-work distortion.
"September 2008."
Includes bibliographical references (p. 27-29).
Also available in PDF from the NBER World Wide Web site (www.nber.org).
Mode of access: Internet.
Keywords: Income distribution; Earned income tax credit